Anesthesia for Percutaneous Radiofrequency Tumor Ablation (PRFA): A Review of Current Practice and Techniques - Piccioni F; Poli A; Templeton LC; Templeton TW; Rispoli M; Vetrugno L; Santonastaso D; Valenza F (Local and Regional Anesthesia, 2019)
Federico Piccioni,1 Andrea Poli,1 Leah Carol Templeton,2 T Wesley Templeton,2 Marco Rispoli,3 Luigi Vetrugno,4 Domenico Santonastaso,5 Franco Valenza1,6 1Department of Critical and Supportive Care, Fondazione IRCCS Istituto Nazionale dei Tumori, Milan, Italy; 2Department of Anesthesiology, Wake Forest University, Winston-Salem, NC, USA; 3Anesthesia and Intensive Care Unit, V. Monaldi Hospital, Naples, Italy; 4Anesthesia and Intensive Care Unit, Santa Maria della Misericordia University Hospital, Udine, Italy; 5Anesthesia and Intensive Care Unit, M. Bufalini Hospital, Cesena, Italy; 6Department of Oncology and Onco-Hematology, University of Milan, Milan, ItalyCorrespondence: Federico PiccioniDepartment of Critical and Supportive Care, Fondazione IRCCS Istituto Nazionale dei Tumori, Via Venezian 1, Milan 20133, ItalyTel +39 2 23902282Fax +39 2 23903366Email federico.piccioni@istitutotumori.mi.itAbstract: Percutaneous radiofrequency ablation (PRFA) of solid tumors is a minimally invasive procedure used to treat primary or metastatic cancer lesions via needle targeted thermal energy transfer. Some of the most common tumor lesions treated using PRFA include those within the liver, lungs and kidneys. Additionally, bone, thyroid, and breast lesions can also be treated. In most cases, this procedure is performed outside of the operating room in a specialized radiology suite. As a result, the clinician must adapt in many cases to the specific environmental issues attendant to providing anesthesia outside the operating room, including the lack of availability of an anesthesia machine in some cases, and frequently a lack of adequate scavenging and other specialized monitoring and equipment. At this time, routine practice and anesthetic prescriptions for PRFA can vary widely, ranging from patients receiving local anesthesia alone, to monitored anesthesia care, to regional anesthesia, to combined regional and general anesthesia. The choice of anesthetic technique will depend on tumor location and practitioner experience. This review aims to summarize the current state of the art in terms of anesthetic techniques for patients undergoing PRFA of solid tumors.Keywords: anesthesia, conduction, deep sedation, conscious sedation, neoplasms, radiofrequency ablation, radiography, interventional